Kriminalitas Sosial Masyarakat Urban di Kampung Baru Kota Sorong - Subhan, Putri Bulkis; Mardliyah, Uswatul; Tumoka, Isgar Muhamamd Ricky (Papua Journal of Sociology (PJS), 2025)
Criminality Crime is a complex phenomenon that affects the lives of urban communities. This research aims to analyse the factors influencing urban communities' social criminality. Social criminality in Kampung Baru Kota Sorong, and how social criminality affects people's lives. know how social criminality affects people's lives. Methods The research method used is a qualitative method with data collection techniques data collection techniques through interviews and observations. The results showed that factors that influence the social criminality of urban communities in Kampung Baru, Sorong City are the influence of liquor poverty, unemployment, social criminality and the influence of alcohol. Baru Kota Sorong is influenced by liquor poverty, unemployment, lack of education, and environmental influences. In addition, this research also found that the social criminality of urban communities in Kampung Baru has a significant impact on people's lives, such as the significant impact on people's lives, such as increased safety and security concerns. This research is expected to contribute to the development of strategies to prevent and combat social criminality in urban communities. social criminality in urban communities.